Comparison of physical characteristics among english professional and semi-professional soccer players across different leagues - Nicholas Joel Ripley; Jack Fahey; Paul Jones; Jake Batsford; Paul Sindall; Christopher Bramah; Paul Comfort (PLoS ONE, 2025)
The purpose of the present study was to investigate if differences exist in neuromuscular qualities between different leagues in English male soccer. Twenty soccer players (age: 23.3 ± 5.2 years, stature: 180.3 ± 7.0 cm, mass: 82.5 ± 7.7 kg) from English football league two (EFL2). 34 soccer players (age: 25.8 ± 4.3 years, stature: 180.9 ± 5.6 cm, mass: 81.4 ± 8.6 kg) from National league (NL) and 23 soccer players (age: 27.5 ± 4.3 years, stature: 182.1 ± 5.5 cm, mass: 84.1 ± 8.0 kg) from National league North (NLN). Each player completed three to five repetitions of the countermovement jump (CMJ), countermovement rebound jump (CMJRJ) and isometric mid-thigh pull (IMTP). Trivial to small differences were observed in CMJ jump height, CMJ momentum, relative average braking and propulsion force, time to take-off and modified reactive strength index (RSI) (p > 0.265, d = 0.05–0.55). However, moderate to large (p ≤ 0.009, d = 0.94–1.25) differences were observed in countermovement depth. Trivial to moderate differences were observed in absolute and relative peak net force and force at 100 and 250 ms (p ≥ 0.092, d = 0.13–0.63). Trivial to moderate differences were observed in CMJRJ rebound jump height and rebound jump momentum (p ≥ 0.440, d = 0.17–0.41). NLN players had longer rebound contact time and lower rebound RSI, rebound average relative braking and propulsion forces to a large magnitude (p ≤ 0.001, d = 1.18–1.85), with small differences between ELF2 and NL (p > 0.536, d = 0.11–0.39). Lower reactive qualities of NLN players could explain observed leagues, considering their relationship with match scoring situations. All players would be considered weak (<30 N/kg) and practitioners should prioritise lower limb strength across all leagues.